The Mentoring in Developing the Arabic Teaching Materials Based on Android Smart Apps Creator (SAC) to Improve the Professional Competence of the Arabic Teachers - Nurul Wahdah; Marsiah Marsiah; David Noor Abdillah (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2022)
In developing digital teaching materials, some applications can be used including the Smart Apps Creator (SAC) application. Through this application, the process of developing teaching materials can be done more easily because it does not use coding. This activity aims to improve the professional competence of Arabic language teachers in the development of application-based teaching materials. In this community service activity, a Service Learning (SL) approach was used in which, an experience-based approach that involves students in various activities and use their experiences to develop their abilities and skills for communities. Service activities were carried out at MIN 4 Pangkalan Bun and in the hall of the Ministry of Religion's Office in Regency of West Kotawaringin. The stages carried out consist of pre service, during service, and post service. The results of this community service activity can be explained as follows. 1. Teachers get benefits from mentoring activities in the form of the ability to produce teaching and evaluation materials output by using the Smart Apps Creator application. 2. Teachers can develop their own further materials by using templates that they have made by themselves. 3. The professional competence of teachers increased through their success in developing teaching materials using applications. 4. The obstacles faced by teachers in using the application are more technical matters that can be overcome during the mentoring.